The reciprocal impact of both visual and verbal metaphors in advertisements: the moderating role of need for cognition. Issue 4 (2nd October 2019) - Kim, Soojin; Park, Sun-Young
Abstract: Metaphors, one of the attractive strategies in communication, can have a significant impact visually and verbally on the persuasion of targeted consumers. The current study investigates the interaction effects when using pictorial and verbal metaphors in ads on consumers' attitude toward the ad, the brand, and purchase intention while considering the moderating effect of individuals' differences in need for cognition (NFC). Experimental results indicate the reciprocal impact of metaphor in both image and copy in ads under different combination-conditions considering the individual differences in information processing (i.e. NFC) with low-involvement products. Furthermore, the results highlight a significant three-way interaction effect on the consumers' attitudes toward the ad and the brand with the individuals' differences in the NFC. The findings illustrate the effective combination and the optimisation of visual and verbal metaphors in order to enhance the ad effects with metaphors. The implications and limitations are discussed.